2008
DOI: 10.1091/mbc.e07-12-1269
|View full text |Cite
|
Sign up to set email alerts
|

GEF-H1 Couples Nocodazole-induced Microtubule Disassembly to Cell Contractility via RhoA

Abstract: The RhoA GTPase plays a vital role in assembly of contractile actin-myosin filaments (stress fibers) and of associated focal adhesion complexes of adherent monolayer cells in culture. GEF-H1 is a microtubule-associated guanine nucleotide exchange factor that activates RhoA upon release from microtubules. The overexpression of GEF-H1 deficient in microtubule binding or treatment of HeLa cells with nocodazole to induce microtubule depolymerization results in Rho-dependent actin stress fiber formation and contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
285
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(315 citation statements)
references
References 32 publications
29
285
1
Order By: Relevance
“…Disruption of microtubules results in activation of RhoA signaling via the microtubule-associated swap over factor GEF-H1 (24). In an earlier study in fibroblasts, we showed RhoAdependent CTGF induction when the microtubules were disrupted by colchicine or nocodazole (25,26).…”
Section: Introductionmentioning
confidence: 64%
“…Disruption of microtubules results in activation of RhoA signaling via the microtubule-associated swap over factor GEF-H1 (24). In an earlier study in fibroblasts, we showed RhoAdependent CTGF induction when the microtubules were disrupted by colchicine or nocodazole (25,26).…”
Section: Introductionmentioning
confidence: 64%
“…3A). We then compared the shape-dependent differentiation of cells that were treated with nocodazole, a potent microtubule depolymerizing agent that has been shown to increase cell contractility (34). Indeed, the drug removed the influence of shape and in all cases gave a strong preference for osteogenesis (>80%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work (9) has shown that there is significant signaling activation and cytoskeletal rearrangement while the traction stress reaches a plateau over this time interval. Dynamic MTs have been shown to regulate Rho guanine nucleotide exchange factor (RhoGEF) activity, and the activation of Rho kinase (33,34) and the Rho/Rho kinase (ROCK) pathway is known to regulate contractility in multiple cell types by modulating myosin phosphorylation (33,35). We therefore hypothesized that the enhancement of traction stress by inhibition of MT dynamics might be caused by the up-regulation of Rho-ROCK activity, which would then increase contractility at the T-cell contact zone.…”
Section: Mt Network Forms a Radially Emanating Dynamic Array During Tmentioning
confidence: 99%